2002
DOI: 10.1073/pnas.042454899
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the guanine nucleotide-binding activity of tissue transglutaminase and its regulation of transamidation activity

Abstract: Tissue transglutaminase (TG) is a Ca 2؉ -dependent acyltransferase with roles in cellular differentiation, apoptosis, and other biological functions. In addition to being a transamidase, TG undergoes a GTP-binding͞GTPase cycle even though it lacks any obvious sequence similarity with canonical GTP-binding (G) proteins. Guanine nucleotide binding and Ca 2؉ concentration reciprocally regulate TG's transamidation activity, with nucleotide binding being the negative regulator. Here we report the x-ray structure de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
415
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 315 publications
(431 citation statements)
references
References 44 publications
9
415
0
2
Order By: Relevance
“…It was a surprise that TG2-I presented functional nucleotide sensitivity similar to the wild type TG2 despite its weak GTP binding while TG2-T presented slightly higher nucleotide binding affinity and accordingly higher GTP sensitivity compared to the wild type. One possibility is that the interaction of BODIPY-GTPγS with non canonical nucleotide binding sites of TG2 does not lead to the increases of its fluorescent intensity (Kiraly et al 2009;Liu et al 2002) or the slight difference between the natural and labelled nucleotides could be responsible for these deviances. It cannot be excluded either that the replacement of Trp 332 , similarly to Cys 277 , may break the integrity and balance of the highly conserved interface between the 159-173 nucleotide binding loop and the amino acids surrounding the active site (Murthy et al 2002) modifying the affinity of nucleotide binding while still keeping its regulatory function.…”
Section: Tg2-i Has Weak Nucleotide Binding Without Functional Consequmentioning
confidence: 99%
“…It was a surprise that TG2-I presented functional nucleotide sensitivity similar to the wild type TG2 despite its weak GTP binding while TG2-T presented slightly higher nucleotide binding affinity and accordingly higher GTP sensitivity compared to the wild type. One possibility is that the interaction of BODIPY-GTPγS with non canonical nucleotide binding sites of TG2 does not lead to the increases of its fluorescent intensity (Kiraly et al 2009;Liu et al 2002) or the slight difference between the natural and labelled nucleotides could be responsible for these deviances. It cannot be excluded either that the replacement of Trp 332 , similarly to Cys 277 , may break the integrity and balance of the highly conserved interface between the 159-173 nucleotide binding loop and the amino acids surrounding the active site (Murthy et al 2002) modifying the affinity of nucleotide binding while still keeping its regulatory function.…”
Section: Tg2-i Has Weak Nucleotide Binding Without Functional Consequmentioning
confidence: 99%
“…These residues have been identified following a mutagenesis approach (indicated by the asterisk in Figure 2A) [20] and by X-ray studies of TGase2 complexed with GDP (indicated by the circles in Figure 2A) [13,14]. We observed that the key residues interacting with GTP in TGase2 (Ser-171, Phe-174 and Arg-476/478/578) are either identical or conservatively replaced in TGase5 (Ser-172, Trp-175 and Lys-510/512/613).…”
Section: Sequence Alignments Of Tgases Predicted Structural Model Ofmentioning
confidence: 99%
“…The inactive conformation of TGase2 shows the nucleophilic Cys-277 hydrogen-bonded to Tyr-516, and the same interaction may well exist between Cys-278 and His-550 in TGase5. Liu et al [13] have suggested that when Ca 2+ binds to TGase2, the β-barrel 1 domain moves away from the catalytic core breaking this hydrogen bond and opening up the transamidation catalytic pocket. A similar mechanism may explain why Ca 2+ binding in TGase5 down-regulates GTP hydrolysis.…”
Section: Guanine-adenine Nucleotide Inhibition Of Tgase2 Tgase3 and mentioning
confidence: 99%
See 1 more Smart Citation
“…human factor XIIIa (hfXIIIa) , TGase 2 (Liu et al, 2002), TGase 3 enzymes (Ahvazi et al, 2002;2003), and a fish enzyme (fTG, equivalent to mammalian TGase 2, Noguchi et al, 2001). All consist of four domains that are similar in organization and fold ( Figure 1a, b for TGase 3): the amino terminal β-sandwich domain; the catalytic core domain which contains the conserved active site triad of Cys272, His330 and Asp353 (using TGase 3 residue numbers); the β-barrel 1 domain; and the β-barrel 2 domain at the carboxy terminus.…”
Section: Introductionmentioning
confidence: 99%